Dural arteriovenous fistula presenting with progressive dementia and parkinsonism. (2nd June 2014) - Fujii, Hiroki; Nagano, Yoshito; Hosomi, Naohisa; Matsumoto, Masayasu
Abstract : We report a rare case of progressive parkinsonism and cognitive dysfunction due to dural arteriovenous fistula (DAVF). A 69-year-old man, with a history of hypertension and diabetes, was admitted to our hospital because of parkinsonism and dementia. Susceptibility-weighted imaging (SWI) revealed a thrombus in the superior sagittal sinus (SSS) and marked dilation of the medullary vein suggestive of the presence of comorbid DAVF. A single-photon emission CT (SPECT) showed widespread hypoperfusion in the bilateral frontal lobes. Selective cerebral angiography revealed a DAVF in SSS. These symptoms were significantly ameliorated following transvenous embolisation of the venous sinus at the shunting point. Reversible parkinsonism and dementia after embolisation was correlated with decreased dilation of medullary vein on SWI and improved cerebral blood flow on SPECT in the frontal lobes. Differentiation of parkinsonian and dementia symptoms due to DAVF from those associated with neurodegenerative disease is of great importance because DAVF-associated deficits may be reversed by endovascular therapy.